Application of the Fama-French three-factor model for a five stocks portfolio in the US stock market - Guillen Paredes, Lizandra Maria (European Scientific Journal, ESJ, 2025)
This paper evaluates the applicability of the Fama-French three-factor model in optimizing portfolio construction and maximizing returns, using historical stock data from various industries over the period from 2002 to 2022. The analysis is divided into two distinct sub-periods, 2002-2012 and 2013-2022, to assess the model’s performance across different economic conditions. The study identifies the market risk premium (Mkt-RF) as the most significant determinant of portfolio returns, especially prominent during the 2013-2022 period. The size premium (SMB) exhibited a negative correlation with portfolio returns, indicating an underperformance of large-cap stocks relative to small-cap stocks, especially in the later period. In contrast, the value premium (HML) was found to be statistically insignificant, suggesting that the value factor did not substantially impact portfolio returns during this time frame. These results underscore the importance of market exposure and the consideration of size factors in portfolio construction while also highlighting the limited impact of the value factor in recent years. The study provides actionable insights for first-time investors and portfolio managers seeking to refine investment strategies based on the dynamics of market risk, size, and value factors. First of all, this indicates the need to align a portfolio with wide market trends by using an index fund or ETF to gain the benefit arising from market risk premium. It also underlines that a balance has to be created between large-cap and small-cap shares to have the returns optimized under specific market conditions. This, in turn, suggests that dependence on the value factor has to be dynamic, anchoring growth stocks in innovative-driven markets but keeping an eye on any change in the economic cycle. These thus provide actionable insights into refining investment approaches with the use of the Fama-French model as a foundational tool.